الثابت والمتغير في أحكام فقه الأسرة من منظور الفقه - ابن حفاف خيرة; دكاني أمال; د/بن السايح محمد (جامعة عمار ثليجي الاغواط, 2023)
ملخص اللغة العربية: يعتبر الثابت والمتغير في أحكام فقه الأسرة من منظور الفقه الإسلامي من أهم المواضيع التي تطرح في الحياة المعاصرة فالثوابت أصول ودعائم تحمي الأسرة من الضياع والسقوط لأنها من مصدر رباني ثابت أما المتغي ا رت فهي حلول تحفظ التوازن وتساعد الأسرة على الاستق ا رر مع ما يحيط بها من تطو ا رت وتحولات ويتم ذلك بتغير بعض أحكامها كي تتماشي مع هذه المستجدات والأحداث فيكون التغير في الجزئيات و التفصيلات البسيطة تماشيا مع موجبات التغير المتمثلة في الزمان والمكان والأع ا رف والأحوال وغيرها ويكون كل هذا ضمن ضوابط وأساسيات وأصول لا يمكن تجاوزها أو التغاضي عنها لتحفظ للأسرة كيانها الإسلامي المستقل وفي نفس الوقت لا تتخلف عن ضروريات الحياة. Abstract: In Islamic jurisprudence, the concepts of constant and variable are considered to be among the most important topics in family jurisprudence, in contemporary life. The constants are the principles and foundations that protect the family from loss, dispersion and fragmentation, as they come from a steady divine source. Variables, on the other hand, are solutions that maintain balance and help the family to remain stable amidst the developments and circumstances, This is achieved by changing some of its rulings to align with these developments and events. These changes would occur in minor details and simple specifics, in accordance with the requirements of change, such as time, place, customs, circumstances and so on. All of these changes must be made within the framework of rules, fundamentals, and principles that cannot be bypassed or overlooked, in order to preserve the independent Islamic identity of the family while also meeting the necessities of life. Keywords : Islamic jurisprudence, constant, variable, family jurisprudence.